Pelatihan Pembuatan Video Animasi Pembelajaran dengan Canva untuk Meningkatkan Keterampilan Digital Guru - Hakim, Abdul; Abdul Haling; Hisanan, Herawan; Nurwahyuningsih; Yanti, Nur Eva (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2025)
The purpose of this PKM is to increase the interest of SMA 4 teachers in Gowa Regency in developing canva-based learning media and improving skills in developing learning media. The methods carried out in this activity consist of: (a) Training, which is an interactive activity with SMA 4 teachers in Gowa Regency to provide theoretical explanations about learning media, and (b) Practice, giving tasks to teachers to create learning animation video media using the Canva application then asking the trainees to collect media assignments to be given assessments and inputs. The results of the service activity of making learning animation videos using the Canva application for SMA 4 teachers in Gowa Regency were attended by 32 participants consisting of teachers and education staff at SMA Negeri 4 Gowa which is located at Jl. Pendidikan, Malino, Kec. It can be concluded that the service activities have an impact on the participants by increasing the interest of teachers in developing canva-based learning media and improving their skills in developing canva-based learning media.